A Critical Analysis of Chromotherapy and Its Scientific Evolution. Issue 4 (2005) - Azeemi, Samina T. Yousuf; Raza, Mohsin
Abstract : Chromotherapy is a method of treatment that uses the visible spectrum (colors) of electromagnetic radiation to cure diseases. It is a centuries-old concept used successfully over the years to cure various diseases. We have undertaken a critical analysis of chromotherapy and documented its scientific evolution to date. A few researchers have tried to discover the underlying scientific principles, but without quantitative study. Sufficient published material can be found about the subject that provides a complete system of treatment focused on the treatment methodologies and healing characteristics of colors. A number of studies have elaborated the relationship between the human body and colors. We also show the possibility of carrying out diverse research into chromotherapy that is pertinent to deciphering the quantum mechanical dipole moment of water molecules. The quantum mechanical dipole moment as a result of the absorption of different colors, we conjecture, produces charge quantization phenomena. This review illustrates that the development of science in the field of electromagnetic radiation/energy can be very helpful in discovering new dimensions of this old theory.